Properties of sintered glass-ceramics prepared from plasma vitrified air pollution control residues - Roether, Judith; Daniel, D. J.; Rani, D. Amutha; Deegan, D. E.; Cheeseman, Christopher R.; Boccaccini, Aldo R. (Journal of Hazardous Materials, 2010)
Air pollution control (APC) residues, obtained from a major UK energy from waste (EfW) plant, processing municipal solid waste, have been blended with silica and alumina and melted using DC plasma arc technology. The glass produced was crushed, milled, uni-axially pressed and sintered at temperatures between 750 and 1150 °C, and the glass-ceramics formed were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Mechanical properties assessed included Vickers's hardness, flexural strength, Young's modulus and thermal shock resistance. The optimum sintering temperature was found to be 950 °C. This produced a glass-ceramic with high density (∼2.58 g/cm3), minimum water absorption (∼2%) and relatively high mechanical strength (∼81 ± 4 MPa). Thermal shock testing showed that 950 °C sintered samples could withstand a 700 °C quench in water without micro-cracking. The research demonstrates that glass-ceramics can be readily formed from DC plasma treated APC residues and that these have comparable properties to marble and porcelain. This novel approach represents a technically and commercially viable treatment option for APC residues that allow the beneficial reuse of this problematic waste. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.proper
Keywords: Air pollution control residues; Energy from waste; Glass-ceramics; Hazardous waste treatment; Plasma vitrification